Discontinuation of treatment and retreatment of neovascular age-related macular degeneration in the real-world: Bundang AMD cohort study report 5 - Cho, Soo Chang; Park, Kyu Hyung; Park, Sang Jun; Joo, Kwangsic; Woo, Se Joon (Frontiers in Medicine, 2023)
Introduction: This single-center retrospective cohort study investigated the incidence rate and risk factors of discontinuation of anti-vascular endothelial growth factor (VEGF) injections and retreatment in typical neovascular age-related macular degeneration (tnAMD) and polypoidal choroidal vasculopathy (PCV) in the real-world setting. Methods: A total of 488 eyes with either tnAMD (n=334) or PCV (n=154) followed up ≥3 years were analyzed. The discontinuation of treatment was defined as the cessation of anti-VEGF injections for one year or longer. Eyes with discontinuing treatment were subdivided into 1) group A: eyes with stable response (complete resolution + incomplete resolution) and 2) group B: those with no expectation of visual gain or poor response. The proportion and median time of discontinuation of treatment or retreatment were analyzed. The visual prognosis and the associated risk factors for the discontinuation of treatment or retreatment were also investigated. Results: Mean follow-up period was 8.1 ± 3.4 years. Of 488 eyes, discontinuation of the treatment occurred in 322 eyes (66.0%) and the median time to the discontinuation was 1.5 years after the initial injection. Of 297 eyes with discontinuing treatment excluding 25 eyes with vitrectomy or photodynamic therapy after discontinuation of the injection, 277 eyes were group A and the remaining 20 eyes were group B. Of the 277 eyes discontinuing treatment with stable response, 185 eyes (66.8%) had retreatment. The median time to retreatment was 3.3 years after the discontinuation of the injections. PCV and the lower annual number of injections were the significant factor associated with the discontinuation. Younger age, male gender, and PCV were the significant factors for the retreatment. Conclusions: Our long-term real-world study suggests that in two thirds of neovascular age-related macular degeneration (nAMD) patients, anti-VEGF treatment could be discontinued 1.5 years after initial treatment and that long-term follow-up and regular monitoring are needed to detect the recurrence.